Comparison of the Effectiveness of Progressive Muscle Relaxation Training and Mindfulness-Based Stress Reduction Training on the Modification of Tinnitus Symptoms and Anxiety Sensitivity in Individuals with Tinnitus - Khoshnood, Mojgan; Agahheris, Mojgan; Rahmanian , Mahdieh; Rafiepoor, Amin; Ghodrati Mirkouhi , Mehdi (KMAN Counseling & Psychology Nexus, 2026)
Tinnitus disorder, with its chronic and multidimensional nature, is not merely an auditory challenge but a biopsychosocial phenomenon that adversely affects patients’ quality of life. Given that anxiety sensitivity plays a significant role in the exacerbation and persistence of this disorder, the present study aimed to compare the effectiveness of two psychological interventions—progressive muscle relaxation (PMR) training and mindfulness-based stress reduction (MBSR) training—on tinnitus symptoms and anxiety sensitivity in individuals with tinnitus. The present study employed a quasi-experimental design with pretest, posttest, and three-month follow-up, including a control group. The statistical population consisted of 45 individuals who referred to Amir A’lam Hospital in Tehran in 2025, selected through purposive sampling and randomly assigned to three groups (two experimental groups and one control group). The research instruments included the Tinnitus Handicap Inventory (THI) and the Anxiety Sensitivity Index–Revised (ASI-3). Data were analyzed using repeated-measures analysis of variance and Bonferroni post hoc tests. The results indicated that both PMR and MBSR interventions led to significant reductions in tinnitus and anxiety sensitivity scores at the posttest and follow-up stages, whereas no significant change was observed in the control group. The difference in effectiveness between the two experimental interventions was not statistically significant, suggesting comparable efficacy of both approaches. The findings underscore the importance of non-pharmacological mind–body interventions in the management of tinnitus and demonstrate that both relaxation training and mindfulness training can be incorporated as cost-effective and efficient treatments within comprehensive tinnitus rehabilitation programs.